Avaliação da atividade antifúngica, citotóxica e mutagênica dos monoterpenos R - (+)-β-citronelol e S - (-) β-citronelol - Silva, Daniele de Figuerêdo (2020)
The frequency and substantial morbimortality of invasive hospital infections caused by Candida spp. stimulate interest in the research of new antifungal drugs that may improve this scenario, which is partly a reflection of the ineffectiveness that current antifungals have shown in recent decades due to resistance mechanisms imposed by these yeasts. Terpenes consist of one of the natural product classes, precursor of numerous biologically active molecular compounds that have already led to the development of drugs. Of the monoterpenes, β-citronelol has shown numerous pharmacological properties that highlights it as a possible candidate for drugs for various therapeutic purposes. However, this compound presents optical isomery and little is studied about the behavior of its isomers in biological environments. In view of these premises, the antifungal, cytotoxic and mutagenic activity of monoterpenes R - (+) - β-citronellol and S - (-) - β-citronellol was evaluated. Several microbiological assays were performed in vitro against Candida albicans and Candida tropicalis strains to evaluate its antifungal performance. The tests used were: determination of the Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC), growth kinetics, mechanism of action, association and inhibition of biofilm formation. For the in vitro study of toxic effects, the following were performed: analysis of cell hemolysis of the ABO system to verify cytotoxic behavior and quantification of nuclear alterations in human oral mucosa cells to analyze the performance of these isomers as genotoxic/mutagenic agents. In the anti-Candida spp. activity assays, both isomers presented MIC50% of 64 μg/mL and MFC50% of 256 μg/mL for Candida albicans. For Candida tropicalis strains, the isomers exhibited a MIC50% of 256 μg/mL and a MFC50% of 1024 μg/mL. The antifungal activity displayed was of fungicidal nature without any statistical difference between the results. Growth kinetics showed that the higher the concentration used of these monoterpenes, the lower the time required to prevent the colony formation. The isomers acted in these cells causing damage to the fungal membrane. The association with amphotericin B demonstrated different effects between the analyzed fungal strains. However, the synergism and aditivity found suggest that the compounds can be used to reduce the fungal resistance of planktonic cells and the formation of biofilm, since all subinhibitory concentrations inhibited the development of this mechanism of virulence and resistance. Regarding the toxic behavior, it was found that both isomers have low cytotoxicity on the erythrocytes of the ABO system. This low hemolytic activity is not due to any kind of protective mechanism in the surface of erythrocytes, but rather because of the simple fact that these substances are not toxic. In addition, isomers caused very few nuclear changes, which makes them compounds with little genotoxic/mutagenic capacity. Thus, due to the antifungal activity and low toxic potential that these isomers presented, these can be considered as candidates for the development of new antifungal therapeutic alternatives, provided that more detailed studies are carried out to make the bioactivity and toxicity profiles of R and S - β - citronellol more solid against Candida species